Preparation of Pyrolytic Carbon Coating from Acetylene by Cold Wall Chemical Vapour Deposition Process - Zhao, Song; Shi, Jingli; Wei, Xinghai; Yan, Xi; Guo, Quangui; Liu, Lang (Asian Journal of Chemistry, 2012)
Pyrolytic carbon coatings from acetylene were deposited on carbon monofilaments at different temperatures by cold wall chemical vapour deposition equipment. The morphology and microstructure of coatings were investigated by scanning electron microscopy and Raman spectroscopy. The results indicate that the increase of temperature from 1273 to 1773 K promotes the crystallization of pyrolytic carbon. Following the "particle-filler" model of carbon formation, it can be explained that the increase of temperature is famous for the elimination of amorphous carbon and crystallization of pyrolytic coating through the inhibition of formation of small linear hydrocarbons in the gas phase.